2004
DOI: 10.1037/0278-7393.30.6.1290
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plausibility on Eye Movements in Reading.

Abstract: Readers' eye movements were monitored as they read sentences describing events in which an individual performed an action with an implement. The noun phrase arguments of the verbs in the sentences were such that when thematic assignment occurred at the critical target word, the sentence was plausible (likely theme), implausible (unlikely theme), or anomalous (an inappropriate theme). Whereas the target word in the anomalous condition provided evidence of immediate disruption, the effect of the target word in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
379
11
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(440 citation statements)
references
References 40 publications
48
379
11
2
Order By: Relevance
“…In contrast, for both sets of analyses for orthographically familiar words there was no difference in prior fixation duration between the frequent and infrequent conditions (ts < 1). 6 It has been suggested that parafoveal-on-foveal effects can sometimes occur as a result of inaccurate saccade targeting (Drieghe et al, 2007;Rayner, Warren et al, 2004;Rayner, White et al, 2003). However, if the parafoveal-on-foveal effects reported above had arisen due to mistargeting of saccades, then there perhaps also should have been a parafoveal-on-foveal effect of word frequency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for both sets of analyses for orthographically familiar words there was no difference in prior fixation duration between the frequent and infrequent conditions (ts < 1). 6 It has been suggested that parafoveal-on-foveal effects can sometimes occur as a result of inaccurate saccade targeting (Drieghe et al, 2007;Rayner, Warren et al, 2004;Rayner, White et al, 2003). However, if the parafoveal-on-foveal effects reported above had arisen due to mistargeting of saccades, then there perhaps also should have been a parafoveal-on-foveal effect of word frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies using isolated word processing (Kennedy, 1998(Kennedy, , 2000Kennedy, Pynte, & Ducrot, 2002) and sentence reading (Kennedy & Pynte, 2005;Kliegl et al, 2006;Pynte & Kennedy, 2006) tasks have suggested that word frequency can also produce such effects. However other studies have shown inconsistent (Hyönä & Bertram, 2004) or no (Calvo & Meseguer, 2002;Henderson & Ferreira, 1993;Rayner, Fischer, & Pollatsek, 1998;Schroyens, Vitu, Brysbaert, & d'Ydewalle, 1999) parafovealon-foveal effects of word frequency, and other research has shown no evidence of other lexical parafoveal-on-foveal effects (Altarriba, Kambe, Pollatsek, & Rayner, 2001;Hyönä & Häikiö, 2005;Inhoff et al, 2000;Rayner, 1975;Rayner, Juhasz et al, 2007) (for reviews see : Rayner, White, Kambe, Miller, & Liversedge, 2003;Rayner & Juhasz, 2004).…”
Section: Models Of Eye Movement Control During Readingmentioning
confidence: 99%
“…As discussed in the Introduction, any erroneous assignment of fixations to neighboring words due to limits of spatial resolution of the eye tracker or inaccuracies associated with its calibration could generate parafoveal-on-foveal effects (see Rayner et al, 2004b, for a cautionary note along those lines).…”
Section: Binocular Control Analysesmentioning
confidence: 99%
“…In this framework, L2 comprehension difficulties may thus be accounted for by absent (or slower) primary semantic integration in L2. We would expect eye-tracking studies to validate this hypothesis by showing that fast and early disruptive effects of semantic violations on eye movements are absent in L2 (Rayner et al, 2004;Warren & McConnell, 2007;Warren et al, 2008).…”
Section: P2 Time-windowmentioning
confidence: 99%